The Antiviral Molecule 5-Pyridoxolactone Identified Post BmNPV Infection of the Silkworm, Bombyx mori - Hua, Xiaoting (Int J Mol Sci, 2021)
Bombyx mori nucleopolyhedrovirus (BmNPV) is a pathogen that causes great economic losses in sericulture. Many genes play a role in viral infection of silkworms, but silkworm metabolism in response to BmNPV infection is unknown. We studied BmE cells infected with BmNPV. We performed liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS)-based non-targeted metabolomics analysis of the cytosolic extract and identified 36, 76, 138, 101, 189, and 166 different molecules at 3, 6, 12, 24, 48, and 72 h post BmNPV infection (hpi) compared with 0 hpi. Compounds representing different areas of metabolism were increased in cells post BmNPV infection. These areas included purine metabolism, aminoacyl−tRNA biosynthesis, and ABC transporters. Glycerophosphocholine (GPC), 2-hydroxyadenine (2-OH-Ade), gamma-glutamylcysteine (γ-Glu-Cys), hydroxytolbutamide, and 5-pyridoxolactone glycerophosphocholine were continuously upregulated in BmE cells post BmNPV infection by heat map analysis. Only 5-pyridoxolactone was found to strongly inhibit the proliferation of BmNPV when it was used to treat BmE cells. Fewer infected cells were detected and the level of BmNPV DNA decreased with increasing 5-pyridoxolactone in a dose-dependent manner. The expression of BmNPV genes ie1, helicase, GP64, and VP39 in BmE cells treated with 5-pyridoxolactone were strongly inhibited in the BmNPV infection stage. This suggested that 5-pyridoxolactone may suppress the entry of BmNPV. The data in this study characterize the metabolism changes in BmNPV-infected cells. Further analysis of 5-pyridoxolactone, which is a robust antiviral molecule, may increase our understanding of antiviral immunity.